Akt and ERK1/2 pathways are components of the vasopressin signaling network in rat native IMCD - Trairak Pisitkun; Vinitha Jacob; Stephen M. Schleicher; Chung‐Lin Chou; Ming‐Jiun Yu; Mark A. Knepper (2008)
Vasopressin regulates water excretion through effects on the renal collecting duct. Vasopressin signaling in the inner medullary collecting duct (IMCD) is mediated by V2 receptor occupation coupled to the generation of cyclic AMP. Here, we employ a "systems" approach to analysis of vasopressin signaling. The objective is to investigate roles of activation of the Akt and ERK1/2 MAP kinase pathways, as well as Ca2+ mobilization, in IMCD cells isolated from rat kidney. The V2 receptor-selective vasopressin analog dDAVP increased the state of Akt activation (increased phosphorylation at T308 and S473) and decreased the state of ERK1/2 activation (decreased phosphorylation at T202 and Y204). Akt activation was blocked by an inhibitor of PI3K, LY294002. In microdissected IMCD segments, nonperiodic spike-like increases in intracellular Ca2+ (FLUO-4) were accelerated by vasopressin. Chelation of Ca2+ or calmodulin inhibition markedly decreased Akt phosphorylation. Decreased ERK1/2 phosphorylation was associated with a decrease in MEK1/2 phosphorylation and an increase in c-Raf phosphorylation at S259 (an inhibitory site). Based on the current findings integrated with previous findings in the IMCD, we now report a 33-node vasopressin signaling network involved in vasopressin regulation of IMCD function.